2008
DOI: 10.1063/1.2839308
|View full text |Cite
|
Sign up to set email alerts
|

Local tuning of photonic crystal cavities using chalcogenide glasses

Abstract: We developed a method to locally tune refractive index in photonic crystals. The technique, based on photodarkening of chalcogenide glasses, enables 3nm resonance tuning of GaAs photonic crystal cavities operating at 940nm.Photonic crystals represent one of the most promising platforms for on chip integration [1] of optical components. However, they are very sensitive to fabrication imperfection, so a practical method to post-tune their optical properties is needed. Here we present such a method based on chalc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 21 publications
0
67
0
2
Order By: Relevance
“…There are a variety of methods of coupling to and from a microsphere and these are described in references [8][9][10][11]20]. We found that free space pumping of the sphere was most convenient in our initial trials to achieve laser action, though this had the disadvantage that only the incident light on the sphere could be accurately measured and the true absorbed power and hence laser thresholds were not obtained.…”
Section: Methodsmentioning
confidence: 98%
“…There are a variety of methods of coupling to and from a microsphere and these are described in references [8][9][10][11]20]. We found that free space pumping of the sphere was most convenient in our initial trials to achieve laser action, though this had the disadvantage that only the incident light on the sphere could be accurately measured and the true absorbed power and hence laser thresholds were not obtained.…”
Section: Methodsmentioning
confidence: 98%
“…Various postprocessing tuning techniques have been demonstrated, such as differential thermal tuning, 7,8 wet chemical digital etching, 9 atomic layer deposition, 10 atomic force microscope nano-oxidation, 11 liquid crystal infiltration, 12 and photodarkening of a chalcogenide glass placed on top of the microcavity. 13 Most of these techniques either modify the properties of the whole sample, which prevents the local tuning of a single nanocavity, or need extra materials and processing tools.…”
mentioning
confidence: 99%
“…Для резона-тора длиной 12,24 мкм (36 отверстий -из них 26 от-верстий находятся под эллиптическим фрагментом, т.е. A = 8,84 мкм) и В = 0,5 мкм добротность составила ~1,4×10 5 . Минимальное значение A, при котором ещё воз-буждается резонансная мода с добротностью выше 10 3 , составляет 3,4 мкм (10 отверстий под эллип-сом), В = 0,65 мкм.…”
Section: а) б) в) рис 2 распределение Ey в вертикальной плоскости unclassified
“…При создании массива нано-резонаторов [4] высокая точность изготовления ми-нимальных деталей должна быть обеспечена на всей площади массива. Индивидуальная настройка резо-наторов в таком массиве требует дополнительных усилий [5]. Создание на основе нанорезонаторов ди-намических систем также требует сложных техноло-гических решений.…”
Section: Introductionunclassified